Phenotype testing, genome analysis, and metabolic interactions of three lactic acid bacteria strains existing as a consortium in a naturally fermented milk - Rodríguez, Javier; Vázquez, Lucía; Flórez, Ana Belén; Mayo, Baltasar (Frontiers in Microbiology, 2022)
This work reports the characterization of three lactic acid bacteria (LAB) strains ‒Lactococcus lactis LA1, Lactococcus cremoris LA10, and Lactiplantibacillus plantarum LA30‒ existing as a stable consortium in a backslopping-inoculated, naturally fermented milk (NFM). This study aimed at uncovering the biochemical and genetic basis of the stability of the consortium and the cooperativity among the strains during milk fermentation. All three strains were subjected to phenotyping, covering the utilization of carbohydrates, enzyme activity, and antibiotic resistance. The strains were grown in milk individually, as well as in all possible combinations, and the resulting fermented product analysed for sugars, organic acids and volatile compounds. Finally, the genomes of the three strains were sequenced and analysed for genes associated with technological and safety properties. As expected, wide phenotypic diversity was seen between the strains. L. cremoris LA10 was the only strain to reach high cell densities and coagulate milk alone after incubation at 22ºC for 24 h; congruently, it possessed a gene coding for a PrtP-type II caseinolytic protease. Compared to any other fermentation, acetaldehyde concentrations were greater by a factor of six when all three strains grew together in milk, suggesting that its production might be the result of an interaction between them. L. lactis LA1, which carried a plasmid-encoded citQRP operon, was able to utilize milk citrate producing diacetyl and acetoin. No genes encoding virulence traits or pathogenicity factors were identified in any of the strains, and none produced biogenic amines from amino acid precursors, suggesting them to be safe. L. plantarum LA30 was susceptible to tetracycline, although it harbours a disrupted antibiotic resistance gene belonging to the tetM/tetW/tetO/tetS family. All three strains contained large numbers of pseudogenes, suggesting that they are well adapted (“domesticated”) to the milk environment. The consortium as a whole or its individual strains might have a use as a starter or as starter components for dairy fermentations. The study of simple consortia, such as that existing in this NFM, can help reveal how microorganisms interact with one another, and what influence they may have on the sensorial properties of fermented products.